2016
DOI: 10.1371/journal.ppat.1005944
|View full text |Cite
|
Sign up to set email alerts
|

Kingella kingae Expresses Four Structurally Distinct Polysaccharide Capsules That Differ in Their Correlation with Invasive Disease

Abstract: Kingella kingae is an encapsulated gram-negative organism that is a common cause of osteoarticular infections in young children. In earlier work, we identified a glycosyltransferase gene called csaA that is necessary for synthesis of the [3)-β-GalpNAc-(1→5)-β-Kdop-(2→] polysaccharide capsule (type a) in K. kingae strain 269–492. In the current study, we analyzed a large collection of invasive and carrier isolates from Israel and found that csaA was present in only 47% of the isolates. Further examination of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(49 citation statements)
references
References 50 publications
(64 reference statements)
2
47
0
Order By: Relevance
“…The polysaccharide capsules of Streptococcus pneumoniae, Haemophilus influenzae, Neisseria meningitidis, and a variety of other organisms have been extensively studied due to their importance as virulence factors and their effective use as vaccine antigens (15)(16)(17)(18). In K. kingae, four distinct polysaccharide capsules, designated types a, b, c, and d, have been identified (19). Capsule types a and b account for greater than 95% of invasive disease isolates (19,20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The polysaccharide capsules of Streptococcus pneumoniae, Haemophilus influenzae, Neisseria meningitidis, and a variety of other organisms have been extensively studied due to their importance as virulence factors and their effective use as vaccine antigens (15)(16)(17)(18). In K. kingae, four distinct polysaccharide capsules, designated types a, b, c, and d, have been identified (19). Capsule types a and b account for greater than 95% of invasive disease isolates (19,20).…”
mentioning
confidence: 99%
“…In K. kingae, four distinct polysaccharide capsules, designated types a, b, c, and d, have been identified (19). Capsule types a and b account for greater than 95% of invasive disease isolates (19,20). Previous work has demonstrated that the capsule is required for full K. kingae virulence in a juvenile rat model of invasive disease (21,22).…”
mentioning
confidence: 99%
“…The major virulence factor is RtxA, a toxin that has been shown to play a key role in virulence in an animal model of infection and allows the bacteria to breach the respiratory tract and joints (10,11). The second is capsule that is speculated, based on the role of other encapsulated bacteria, to protect the bacterium from the host immune response and to enable mucosal colonization, survival of the organism in the bloodstream, and invasion of deep body sites (12)(13)(14)(15). The other suggested K. kingae virulence factors, which have yet to be studied in an in vivo model of infection, include type IV pili that mediate possible initial adherence (16), KnnH, an adhesin allowing possible respiratory tract attachment (12), and outer membrane vesicles produced during infection that may offer a strategic advantage in breaching the respiratory epithelium (17).…”
mentioning
confidence: 99%
“…The K. kingae strains carried differ in virulence. Some strains belonging to a few distinct genotypic clones and characterized by polysaccharide capsule a or b are responsible for the vast majority of clinical diseases (11). On the other hand, other clones that elaborate capsule type c or d are usually found as mere respiratory colonizers and are rarely isolated from invasive infections (11).…”
mentioning
confidence: 99%
“…Some strains belonging to a few distinct genotypic clones and characterized by polysaccharide capsule a or b are responsible for the vast majority of clinical diseases (11). On the other hand, other clones that elaborate capsule type c or d are usually found as mere respiratory colonizers and are rarely isolated from invasive infections (11). The age-related prevalence of K. kingae colonization parallels that of invasive disease, reaching 10 to 12% during the second year of life and decreasing in older children (4,5).…”
mentioning
confidence: 99%